Control-based Fault Current Limiter for Minimizing Impact of Distributed Generation Units on Protection Systems - Pablo E. Munoz; Ricardo J. Mantz; Sergio A. Gonzalez (Journal of Modern Power Systems and Clean Energy, 2023)
Distributed generation units (DGUs) bring some problems to the existing protection system, such as those associated with protection blinding and sympathetic tripping. It is known that fault current limiters (FCLs) help minimize the negative impact of DGUs on the protection system. In this paper, a control-based FCL is proposed, i.e., the FCL is integrated into the DGU control law. To this end, a predictive control strategy with fault current limitation is suggested. In this way, a DGU is controlled, not only for power exchange with the power grid but also to limit its fault current contribution. The proposal is posed as a constrained optimization problem allowing taking into account the current limit explicitly in the design process as a closed-loop solution. A linear approximation is proposed to cope with the inherent nonlinear constraints. The proposal does not require incorporating extra equipment or mechanisms in the control loop, making the design process simple. To evaluate the proposed control-based FCL, both protection blinding and sympathetic tripping scenarios are considered. The control confines the DGU currents within the constraints quickly, avoiding large transient peaks. Therefore, the impact on the protection system is reduced without the necessity that the DGU goes out of service.